1985
DOI: 10.2105/ajph.75.12.1435
|View full text |Cite
|
Sign up to set email alerts
|

A profile of the self-poisoner in Michigan.

Abstract: We reviewed the charts of all patients (160) ages 15 and older discharged in 1981 from the four hospitals in Lansing, Michigan with a diagnosis of overdose. Females predominated (65 per cent) and the median age was 27 years. The most common reason for intentional self-poisoning was "significant-other" conffict (54.5 per cent), followed by family conflict and financial problems. Benzodiazepines were most commonly used followed by acetylsalicylic acid and ethanol. (Am J Public Health 1985; 75:1435-1436 Introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The only study we could find that looked specifically at the profile of the overdose patient was done in Michigan, USA, in 1985. 1 A subjective evaluation by doctors and nurses at Paarl Hospital indicated that there was a high incidence of patients who had overdosed presenting to this hospital. They found this distressing and felt that there should be an enquiry into the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The only study we could find that looked specifically at the profile of the overdose patient was done in Michigan, USA, in 1985. 1 A subjective evaluation by doctors and nurses at Paarl Hospital indicated that there was a high incidence of patients who had overdosed presenting to this hospital. They found this distressing and felt that there should be an enquiry into the phenomenon.…”
Section: Introductionmentioning
confidence: 99%